2019
DOI: 10.1007/s00265-019-2710-z
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of body size and UV coloration in influencing male-male competition in a lacertid lizard

Abstract: Communication via color signals is common in natural systems. Ultraviolet (UV)-blue patches located on the outer-ventral scales of some Lacertid lizards are thought to be involved in male-male competition. However, the mechanisms that maintain their honesty remain unknown. Here, we use the common wall lizard Podarcis muralis to test whether the lateral UV-blue spots are conventional signals, the honesty of which is guaranteed by receiver-dependent costs, and discuss their potential role as an amplifier of body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 85 publications
2
22
1
Order By: Relevance
“…We have confirmed sexual dimorphism in both quantitative and chromatic parameters of the UV–blue traits in Darevskia lizards. Our results are consistent with other studies on lacertids showing that the blue/UV–blue lateral spots occupy larger area and/or are more numerous in males than in females, for example, Psammodromus algirus ( Carretero 2002 ), G. galloti ( Molina-Borja et al 2006 ), T. lepidus ( Font et al 2009 ), P. muralis ( Names et al 2019 ). Significant sex × species interactions in the LMs confirm that sexual dimorphism in OVS (UV–blue area, spot count, and chromatic parameters) varies considerably across the species ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have confirmed sexual dimorphism in both quantitative and chromatic parameters of the UV–blue traits in Darevskia lizards. Our results are consistent with other studies on lacertids showing that the blue/UV–blue lateral spots occupy larger area and/or are more numerous in males than in females, for example, Psammodromus algirus ( Carretero 2002 ), G. galloti ( Molina-Borja et al 2006 ), T. lepidus ( Font et al 2009 ), P. muralis ( Names et al 2019 ). Significant sex × species interactions in the LMs confirm that sexual dimorphism in OVS (UV–blue area, spot count, and chromatic parameters) varies considerably across the species ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…The same was not proven for the shoulder spots, however, this could have been caused by small sample sizes in this particular subset of data. Despite the high interspecific variability, the GLS model predicts a general tendency of OVS UV–blue area to grow with body size in males, rather than females ( Figure 5 ), which is also consistent with observations in Podarcis lizards ( Names et al 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Andersson, Örnborg, & Andersson, 1998;Siebeck, 2004;Ries et al, 2008;Badiane, Carazo, & Font, 2018) and have a visual system sensitive to UV light (Bowmaker, 2008;Cronin & Bok, 2016). We have now good evidence that UV coloration can be sexually dichromatic (Hunt et al, 1998;Names et al, 2019) and act as honest, condition-dependent Female mate choice for UV reflectance 4 indicator of male quality (e.g. Keyser & Hill, 1999, 2000Griggio, Zanollo, & Hoi, 2010;Pérez i de Lanuza, Carazo & Font, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…UV coloration in lizards seems to function as honest indicator of male quality (e.g. Whiting et al, 2006;Molnár et al, 2012;Pérez i de Lanuza, Carazo, & Font, 2014) and has been shown to influence social aggressiveness, dominance, and contest outcome during male-male competition (Stapley & Whiting, 2006;Bajer et al, 2011;Martin et al, 2016;Names et al, 2019). For example, in European green lizards Lacerta viridis, UV coloration signals male quality (Molnár et al, 2012(Molnár et al, , 2013, determines male fighting success (Bajer et al, 2011), and predicts female mate choice (Bajer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%